The Model of Collaborative Governance in Addressing Poverty in Indonesia - Herman Lawelai; Achmad Nurmandi (Indonesian Journal Publisher, 2022)
The aim of this study is to review and evaluate the implementation of the Model Collaborative Governance in addressing poverty in Indonesia. The study involves secondary data analysis and relevant written sources to assess the effectiveness of this model in addressing poverty. The results of the research indicate that the Model Collaborative Governance can help ensure that poverty alleviation solutions are inclusive and meet the needs of the community. However, for optimal results, there needs to be effective communication and coordination between the government, the private sector, civil society, and community organizations. This study provides an overview of the potential of the Model Collaborative Governance in addressing poverty in Indonesia and provides recommendations for improvement and increased implementation of this model in the future.